Menumbuhkan kewirausahaan budaya: Peluang dan tantangan dalam pendidikan berbasis seni dan budaya - Adriani Yulia Purwaningrum; Nur Hidayanto Pancoro Setyo Putro; Bunga Putri Maulia (Universitas Pendidikan Indonesia, 2026)
Entrepreneurship education has become a key agenda in higher education to foster student creativity and innovation. This study aims to analyze the implementation of arts and culture-based entrepreneurship at Fakultas Bahasa, Seni, dan Budaya (FBSB) Universitas Negeri Yogyakarta. The research used a mixed-methods approach, including student surveys, Forum Group Discussions (FGDs) with lecturers, and analysis of curriculum documents. The results indicate that the majority of students have a high interest and awareness of cultural entrepreneurship, with approximately two-thirds having gained practical experience through class projects and training programs. However, integration within the curriculum remains uneven. The Fine Arts and Crafts Study Program emphasizes cultural innovation, while the Language and Music programs tend to be more general. FGDs with lecturers revealed that FBSB students excel in creativity but are weaker in formal business literacy than students from the Fakultas Ekonomi dan Bisnis. Furthermore, another challenge arises from reliance on artificial intelligence in proposal development, raising issues of originality. This study concludes that contextual curriculum redesign, the implementation of project-based learning, strengthening institutional support, and ethical digital literacy are necessary to foster competitive cultural entrepreneurs in the era of the creative economy.